2020
DOI: 10.1016/j.omtn.2020.01.033
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 Facilitates Oral Squamous Cell Carcinoma Tumorigenesis by Enhancing c-Myc Stability via YTHDF1-Mediated m6A Modification

Abstract: N 6 -Methyladenosine (m 6 A) is the most common internal modification of eukaryotic messenger RNA (mRNA) that occurred on the N 6 nitrogen of adenosine. However, the roles of m 6 A in oral squamous cell carcinoma (OSCC) are still elusive. Here, we investigate the function and mechanism of methyltransferase-like 3 (METTL3) in OSCC tumorigenesis. Clinically, METTL3 was significantly upregulated in tissue samples and correlated with the poor prognosis of OSCC patients. Functionally, loss and gain studies illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 33 publications
(53 reference statements)
7
114
1
Order By: Relevance
“…Recent studies indicate that m6A modification is related to tumorigenesis [12], proliferation [13], invasion [14] and metastasis [15]. In OSCC, research has indicated that METTL3 enhanced OSCC tumorigenesis through YTHDF1mediated m6A modification [16]. However, there are fewer studies to explore the m6A prognostic value in OSCC through analyzing m6A-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that m6A modification is related to tumorigenesis [12], proliferation [13], invasion [14] and metastasis [15]. In OSCC, research has indicated that METTL3 enhanced OSCC tumorigenesis through YTHDF1mediated m6A modification [16]. However, there are fewer studies to explore the m6A prognostic value in OSCC through analyzing m6A-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…METTL3 was considered to be a methyltransferase, part of the methyltransferase complex, and was responsible for the m6A modi cation [27,53].METTL3 was involved in many signal pathways such as PI3K / Akt [31,[54][55][56][57][58], MAPK [22] ,Wnt /beta-Catenin [47,59,60] and p38 / ERK [61]pathways,which were all associated with tumor deterioration. In addition, METTL3 could in uence the development of tumor by regulating some transcription factors or important oncogenes.Studies had found that METTL3 could positively regulate the expression of oncogene EZH2 [24,25,62].It promoted the expression of MYC as well as increased stability of protein by regulating the m6A methylation of MYC mRNA to lead to carcinogenesis in PCA and gastric cancer, promote the occurrence of OSCC tumor and affect the growth and invasion of BCA cells [40,[63][64][65][66].When METTL3 was silenced, it inhibited the activity of the Wnt pathway by reducing the m6A methylation level of LEF1 mRNA and reducing protein expression [59,67].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to ALKBH5, alkB homolog 3 (ALKBH3) has been shown the demethylase activity for 1-methyladenine and 5-methylcytosine (49). m 6 A readers include the YTH domain family (YTHDF), insulin-like growth factor 2 mRNA binding protein 2 (IGF2BP), and HNRNPA2B1 (50). YTHDF proteins act as m 6 A readers, which can maintain the stability of m 6 A transcripts (51, 52) ( Figure 1).…”
Section: Rna Methylation and Kidney Cancer Diverse Modifications Of Rmentioning
confidence: 99%